Serum homocysteine, vitamin B6, B12 and folic acid levels in a rat model of intestinal ischemia-reperfusion - Parmaksiz, M. Ergun; Kazez, Ahmet; Gürsu, M. Ferit; Gülcü, Funda; Özel, Ş. Kerem; Köseo?ullari, A. Aysel (My University, 2005)
Aim: Glutathione increases during ischemia-reperfusion (I/R) and shows many effects in the pathogenesis of this process. One of its effects is to modulate cysteine, which has an important role in the production of homocysteine in the cells. In this experimental study, the levels of homocysteine during intestinal I/R and the vitamins that play a role in its metabolism were investigated. Material and Method: Forty male Wistar-albino prepubertal rats weighing between 90 and 120 gr. were divided into 4 groups. Group 1 (control, n=10) was taken as control. Blood samples were taken without any applied procedure. In group 2 (sham, n=10) abdomen was opened, superior mesenteric artery (SMA) was dissected and then closed. In Group 3 (ischemia, n=10) SMA blood flow was stopped for three hours. In Group 4 (I/R, n=10) the blood flow was maintained again after cessation for 3 hours and blood samples were taken after 3 hours of reperfusion. In all samples, plasma homocysteine, vitamin B6, B12 and folic acid levels were determined. The results were assessed with One-way ANOVA, Scheffe and Tukey HSD tests. Results: The increase of homocysteine levels was significant in ischemia and I/R groups when compared to control and sham groups (p<0.05). However the comparison of results between the ischemia and I/R groups was not significant (p>0.05). The difference of the vitamin levels was not significant between the groups, either (p>0.05). Conclusion: Homocysteine levels increase during ischemia. The levels of vitamins which take part in homocysteine metabolism do not change in the early period. The cut-off levels obtained during intestinal ischemic events can be used to determine the depth of ischemia in clinical practice.
İntestinal iskemi-reperfüzyon modelinde plazma homosistein, vitamin B6, B12 ve folik asit düzeyleri
Keywords: Folic acid; Homocysteine; Intestinal ischemia/reperfusion; Vitamin B12; Vitamin B6